Family as a factor of support for artistically gifted children from the perspective of art faculty students - Кristinka I. Selaković; Biljana D. Radović; Мirko S. Marković (Inovacije u Nastavi, 2025)
The paper discusses the role of the family which, in the complex and dynamic process of forming a child’s personality, is of great importance for creating a stimulating environment and providing adequate support for the development of giftedness. Parents are expected to recognise and support giftedness in their child, which is often a complex and challenging task. The aim of the research was to examine the experience of students regarding the way in which the family encouraged their artistic talent and supported the decision to enroll at an art faculty. Our intention was also to identify the forms of support in relation to the educational status of the parents. The questionnaire designed for the purposes of this research was structured to include, apart from the questions about parental support, students’ opinions regarding cooperation and mutual orientation between the family and the school. The research was conducted with the participation of the fourth-year undergraduate students of the Faculty of Applied Arts, University of Arts in Belgrade (N=103). The results showed that the majority of the respondents received parental support when making a decision to enroll at an art faculty, and that this played a more significant role than the influence of the school and teachers on the development of their artistic talent. In addition, empirical findings indicate the presence of various types of family incentives, support, and stimulation in the field of fine arts and confirm the importance of family for the development of potentially gifted children in the field of fine arts. Regarding the educational status of parents, no statistically significant difference was found between the level of education and the type of support, except for the joint visits to museums, galleries, exhibitions, and trips for the same reason. At the same time, the research raises the issue of promoting cooperation and partnership between parents and schools in providing support to artistically gifted children in the further development of their potential.